Penghitungan Beban Kritis pada Struktur Balok-Kolom Akibat Pembebanan Secara Aksial dan Lateral Berbasiskan Metode Beda Hingga - Eka Satria; N Nusyirwan; Deri Yunifki (Metal: Jurnal Sistem Mekanik dan Termal)
This paper is aimed to determine the critical buckling load of the beam-column structures for practical applications. Firstly, the critical buckling loads is calculated numerically based on finite difference method. For geometrical modeling, the structures are supported in three types of supports; pinned-roller, fixed-free, and fixed-pinned. Then, a geometry of the beam is varied in variation of slenderness ratio. The load is given in types of uniform distribution load, q, laterally and a concentrated load, P, axially. Using a computational program, the relationships of P/q to slendernes ratio, l, for all models are determined. The results then are approached by regression technique of a least square method in order to find a the best fit of equation. This equation is recommended as a practical equation for determining the critical buckling of the beam-column structures under variation of types of supports, slenderness ratio and rasio P/q.